Oxidation and Reduction Dual-Responsive Polymeric Prodrug Micelles Co-delivery Precisely Prescribed Paclitaxel and Honokiol for Laryngeal Carcinoma Combination Therapy - Lanzhu Zhou; Jun Wu; Zhe Sun; Wenzhong Wang (Frontiers Media S.A., 2022)
Laryngeal carcinoma is the most common head and neck malignancy globally, and chemotherapy is still the most common treatment for this type of carcinoma. Monotherapy has become powerless because of the lack of drugs in the anticancer agent library, the difficult process of new drug discovery, and the widespread drug resistance. Combination therapy with two agents, in particular Chinese herbal medicines with chemotherapy drugs, is a potential alternative to chemotherapy alone. However, combination therapy faces difficulties in delivering multiple drugs to tumor tissue in a precise ratio. Here, a cocktail polymeric prodrug micelle (PHPPM) was developed using an oxidation and reduction dual-responsive polymeric paclitaxel (PTX) and polymeric honokiol (HK) prodrugs. Both of them were obtained by covalently conjugating the drug to dextran via diselenium bonds. Following optimization and characterization, the PHPPM with the precise mass ratio of PTX and HK was obtained, enabling ratiometric drug loading, synchronized drug release in response to tumor high-level reactive oxygen species and glutathione environment, long blood circulation, and high tumor accumulation. This co-delivery system can effectively inhibit laryngeal carcinoma growth in vitro and in vivo. Codelivery of chemotherapy agents and Chinese herbal medicine with a precise ratio and controlled release of the two drugs at the tumor site provides an effective approach to clinical therapy for other laryngeal carcinomas.